2008
DOI: 10.1021/jp710352m
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Packing and Solid-State Fluorescence of Alkoxy-Cyano Substituted Diphenylbutadienes:  Structure of the Luminescent Aggregates

Abstract: A detailed study on the photophysical properties of a series of alkoxy substituted diphenylbutadienes in solution and in the solid state providing a molecular level understanding of the factors controlling their solid-state luminescence behavior is reported. Our studies provide clear evidence for exciton splitting in the solid state resulting in red-shifted emission for this class of materials. The role of the number of alkoxy substituents and the alkyl chain length in controlling the nature of the molecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
97
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(106 citation statements)
references
References 95 publications
9
97
0
Order By: Relevance
“…Interestingly, a similar blue shift of the fluorescence maxima was also observed when heating a thin film of (2,1-a)-dispiro(3,4,5-trimethoxyphenylfluorene)-indenofluorene (see Figure S18 in the Supporting Information), which became nearly identical to its emission spectrum in solution (see Figure S9 in the Supporting Information). Similar changes in the solid-state fluorescence spectrum with temperature have been reported for butadiene derivatives [64][65][66] but in these examples, the monomer-like or excimer-like fluorescence come from specific "intermolecular packing", which may be modified with temperature. In a "herringbone" arrangement, minimal electronic coupling between molecules led to a monomer-like emission, whereas in a "brickstone" arrangement, molecular packing led to excimer-like fluorescence.…”
Section: Wwwchemeurjorgsupporting
confidence: 74%
“…Interestingly, a similar blue shift of the fluorescence maxima was also observed when heating a thin film of (2,1-a)-dispiro(3,4,5-trimethoxyphenylfluorene)-indenofluorene (see Figure S18 in the Supporting Information), which became nearly identical to its emission spectrum in solution (see Figure S9 in the Supporting Information). Similar changes in the solid-state fluorescence spectrum with temperature have been reported for butadiene derivatives [64][65][66] but in these examples, the monomer-like or excimer-like fluorescence come from specific "intermolecular packing", which may be modified with temperature. In a "herringbone" arrangement, minimal electronic coupling between molecules led to a monomer-like emission, whereas in a "brickstone" arrangement, molecular packing led to excimer-like fluorescence.…”
Section: Wwwchemeurjorgsupporting
confidence: 74%
“…1,2 Apart from the conventional interactions like hydrogen bonds, salt bridges and hydrophobic interactions, 3,4 other weak nonconventional interactions like CHÁÁÁp, OHÁÁÁp, NHÁÁÁp, and CationÁÁÁp interactions also play vital roles in protein stability. [5][6][7][8][9][10][11] The high incidence of such noncovalent interactions in large biological systems along with their key roles in chemical [12][13][14] and biological recognition processes 15,16 has led to an increasing number of theoretical 17,18 and experimental studies 19,20 devoted to the quantification and characterization of such interactions. Although useful to a certain extent, an accurate experimental description of noncovalent interactions is difficult 21 despite the enormous progress made in experimental techniques in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35] In this regard, small organic derivatives with olefin, acetylene, phenylenevinylene and phenyleneethynylene spacers have found current interest. 19,24,[36][37][38][39][40] Davis et al reported the solid state fluorescence of alkoxy-cyano substituted diphenylbutadiene derivatives. 24 Thomas et al described the photophysical properties of alkoxy substituted phenyleneethynylenes in the solid state.…”
mentioning
confidence: 99%
“…19,24,[36][37][38][39][40] Davis et al reported the solid state fluorescence of alkoxy-cyano substituted diphenylbutadiene derivatives. 24 Thomas et al described the photophysical properties of alkoxy substituted phenyleneethynylenes in the solid state. 40 The solid state fluorescence of some fluorinated diphenylpolyenes was reported by Sonoda et al 37 Lewis and Yang delineated the solid state fluorescence of some single olefin/acetylene spaced diphenyl derivatives with carboxamide substituents.…”
mentioning
confidence: 99%